Properties of Structural Lightweight Concrete Filled with Palm-Based Polyurethane - Mohd Sari, Kamarul Aini; Mat, Sohif; Badri, Khairiah; M. Sani, Abdul Rahim (International Journal of Integrated Engineering, 2014)
Four experiments were conducted to characterize the properties of palm-based polyurethane (PU) foam in lightweight concrete. The PU foam was synthesized from palm kernel oil-based polyol reacted with 2, 4-methylene diphenyl diisocyanate. Polyurethane as lightweight aggregate was mixed with ordinary cement, sand, and water to form lightweight concrete. The microstructure of PU aggregate can be accessed from optical micrographs. Density, compressive strength, distribution of fine aggregate, and the interfacial zone were also investigated. The result showed that palm-based lightweight concrete has excellent compressive strength (17.5 MPa), and fulfilled the minimum strength requirement for structural concrete. Palm-based lightweight concrete with 0.6 w/c ratio and 3% w/w PU system achieved 1770 kg/m3 presented uniform dispersion of aggregate and excellent mechanical bonding.